Dynamic rupture process of the 1999 Düzce earthquake - Bekler, Feyza Nur. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2018., 2018)
Rupture process of large magnitude earthquakes have been generally performed by using a kinematic approach. A typical set of input parameters for kinematic approach includes; fault length, fault depth, rupture velocity, slip distribution and rise time defining the slip velocity time function. Kinematic models have been quite successful in obtaining detailed slip distribution maps of large earthquakes. However, the kinematic models have their own disadvantages. One major disadvantage is that the physics of the kinematic inversion scheme is incomplete. One uses representation theorem and Green’s functions approach to obtain slip distribution without considering the forces and the frictional properties on the fault interface. In fact, it is not clear whether the kinematic models of earthquakes with the inverted slip and rise time distributions are physical plausible. This lack of physical constraint on physical properties and the force balance leads to lack of long-term behavioral property of the fault. Dynamic modeling has been proposed as a new perspective to explain complexity of source parameters, rupture radiation pattern and slip distribution. One way of understanding the dynamic and kinematic mechanism of the earthquake source is to model how the rupture process improves. Hence, proper understanding of this process and appropriate modeling approaches play an important role in seismic hazard and seismic mitigation estimations. On the other hand, the modeling of a dynamic rupture process of an earthquake may provide information on how the limitations on the source can be understood.
Keywords: Earthquakes -- Turkey -- Düzce.